The warning - Bunn, T. Davis, 1952- (Thomas Nelson Publishers, 1998)
He had read the passage form Genesis dozens of times, but now the words rose up before him with new and terrifying meaning. The nightmares he'd been having for over two weeks started to make sense, like an image projected on a screen slowly coming into focus. And then, unmistakably, a message. It is coming. Forty-one days. The awful deadline left Buddy frightened and confused. Speaking about what he knew would threaten his job, his family's security, even his life. Besides, who would listen? A prediction that America faced an historic economic collapsed went against every expert's forecast.